Partial characterization of genes encoding the ATP-binding cassette proteins of Cryptosporidium parvum - Chan, L.L.; Fong, M.Y. (2005)
The present study aims to explore the possible mechanisms underlying the multidrug resistance characteristic of Cryptosporidium parvum by detecting the presence of ATP-binding cassette (ABC) protein encoding genes, especially one that shows high similarity to members belonging to the multidrug resistance protein (MDR) and multidrug resistance associated protein (MRP) subfamilies. PCR using ABC-specific degenerate primers successfully amplified two unique fragments, designated Cpnbd1 and Cpnbd2, from C. parvum genomic DNA. Cpnbd1 exhibited high degree of homology (99-100) with the nucleotide- binding domains (NBDs) at the NH2 -terminal halves of two previously reported ABC proteins (CpABC and CpABC1) of human and bovine origin C. parvum isolates. It is likely that CpABC, CpABC1 and Cpnbd1 were encoded by homologous genes of a type of ABC transporter protein found in different C. parvum isolates. However, Cpnbd2 showed moderate levels of similarities (28-49) to the NBDs of four ABC proteins characterised in C. parvum to date. Therefore, Cpnbd2 could be a novel member of an ABC superfamily of proteins in C. parvum. Phylogenetic analyses on a list of ABC transporters known to associate with MDR phenotype has significantly linked Cpnbd1 and Cpnbd2 to these transporters, thus suggesting that Cpnbd1 and Cpnbd2 proteins may contribute to the intrinsic multidrug resistance phenotype of C. parvum